Gene Disruption of Honey Bee Trypanosomatid Parasite, Lotmaria passim, by CRISPR/Cas9 System - Liu, Qiushi; Lei, Jing; Kadowaki, Tatsuhiko (Frontiers in Cellular and Infection Microbiology, 2019)
Two trypanosomatid species, Lotmaria passim and Crithidia mellificae, have been shown to parasitize honey bees to date. L. passim appears to be more prevalent than C. mellificae and specifically infects the honey bee hindgut. Although the genomic DNA has been sequenced, the effects of infection on honey bee health and colony are poorly understood. To identify the genes that are important for infecting honey bees and to understand their functions, we applied the CRISPR/Cas9 system to establish a method to manipulate L. passim genes. By electroporation of plasmid DNA and subsequent selection by drug, we first established an L. passim clone expressing tdTomato or Cas9. We also successfully disrupted the endogenous miltefosine transporter and tyrosine aminotransferase genes by replacement with drug (hygromycin) resistant gene using the CRISPR/Cas9-induced homology-directed repair pathway. The L. passim clone expressing fluorescent marker, as well as the simple method for editing specific genes, could become useful approaches to understand the underlying mechanisms of honey bee-trypanosomatid parasite interactions.